The Use of Guided Metacognitive Strategy to Improve Students' Reading Comprehension - Mikhael Misa (Universitas Negeri Malang, 2015)
Abstract: This research aims to identify the implementation of metacognitive strategy to improve EFL of students' reading comprehension of the English Department at University of Timor in an analytical exposition text. This research is Collaborative Classroom Action Research (CAR). The data were gained through field notes, students' reading achievement and interview guide. The results showed that the implementation of metacognitive strategy improved the students' skill in reading analytical expository text especially in determining topic sentence, main idea and supporting idea. The result also revealed that using metacognitive strategy could employ the significant improvement of the students' reading comprehension skills of analytical exposition texts. Key Words: metacognitive strategy, reading comprehension, analytical expository text   Abstrak: Penelitian ini bertujuan untuk mengidentifikasi pelaksanaan strategi metakognitif untuk meningkatkan EFL pemahaman bacaan oleh mahasiswa di Jurusan Bahasa Inggris Universitas Timor dalam teks eksposisi analitis. Penelitian ini menggunakan Penelitian Tindakan Kelas (PTK) Kolaboratif. Data yang diperoleh melalui catatan lapangan, prestasi membaca siswa dan pedoman wawancara. Hasil penelitian menunjukkan bahwa pelaksanaan strategi metakognitif meningkatkan keterampilan siswa dalam membaca analitis teks ekspositori terutama dalam menentukan topik kalimat, gagasan utama dan ide pendukung. Hasil penelitian juga menunjukkan bahwa menggunakan strategi metakognitif dapat meningkatkan dengan signifikan keterampilan pemahaman bacaan oleh siswa tentang teks eksposisi analitis. Kata kunci: strategi metakognitif, pemahaman bacaan, analisis teks ekspositori